2018 MEDAM Assessment Report on Asylum and Migration Policies in Europe. Flexible Solidarity: A comprehensive strategy for asylum and immigration in the EU - Esther Ademmer; Mikkel Barslund; David Benček; Mattia Di Salvo; Dominik Groll; Rezart Hoxhaj; Omar Kadkoy; Mauro Lanati; Nadzeya Laurentsyeva; Matthias Lücke; Lars Ludolph; Chiara Pizzuti; et al. (Kiel Institute for the World Economy (IfW), 2018)
The EU faces major challenges in asylum and migration policy: reorganize the EU asylum system, secure the external border, curb irregular immigration through cooperation with African governments, and support developing countries that host large numbers of refugees from Syria and elsewhere. These challenges are inter-connected and require a comprehensive approach with broad support by all EU member states. However, member states are affected by immigration in substantially different ways and the political preferences of policy makers and voters also vary widely–necessitating implementable proposals to overcome the EU's asylum and immigration impasse. In the '2018 MEDAM Assessment Report', we propose a comprehensive strategy for EU asylum and immigration policies that is both politically feasible and effective, based on the concept of flexible solidarity between EU member states. – – Die EU steht vor großen Herausforderungen in der Asyl- und Migrationspolitik: Reform des EU-Asylsystems, Sicherung der Außengrenzen, Begrenzung der irregulären Einwanderung durch die Zusammenarbeit mit afrikanischen Regierungen sowie Unterstützung von Entwicklungsländern mit einer großen Zahl an Flüchtlingen. Diese Herausforderungen sind miteinander verwoben und erfordern nicht nur einen ganzheitlichen Ansatz, sondern auch die breite Unterstützung aller EU-Mitgliedsstaaten. Dabei sind diese in unterschiedlicher Weise von Einwanderung betroffen, und auch die politischen Ansichten der Entscheidungsträger und Wähler unterscheiden sich erheblich. Es bedarf umsetzbarer Vorschläge, um den aktuellen ,,Stillstand“ in der Asyl-und Migrationspolitik der EU zu überwinden. Im "2018 MEDAM Assessment Report on Asylum and Migration Policies in Europe" schlagen wir eine ganzheitliche Strategie für die EU-Asyl-und Migrationspolitik vor, die sowohl politisch machbar ist als auch auf dem Konzept der flexiblen Solidarität zwischen EU-Mitgliedsstaaten beruht.
Keywords: 320